Guessing Meaning Strategies and Arabic Reading Comprehension Ability Among Chinese College Students - Jun, Wang Xiao; Baharudin, Harun; Awang, Mohd Mahzan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Guessing word meanings is vital for acquiring deep reading and adequate text comprehension, as the study implies that the cross-sectional approach quantitatively assesses the effect of guessing meaning strategies on Chinese university Arabic students' reading performance. There was significant evidence of the perfect relationship between the mastery of the guessing meaning strategy and the improvement of reading comprehension scores presented through the analysis of Chinese universities' data (r = 0.306, p < 0.01). It shows the vital importance of these approaches in raising reading skills. Students are well-positioned to carry out word investigation in terms of the etymology or roots of words, whether they are antonyms, synonyms, or synonymous phrases that help them deduce the meanings of words they are not familiar with and find out the meanings or explanations systematically in their reading. Guessing meaning strategies should be used in the Arabic language teaching curriculum in China to ensure that Arabic instructors can make learning enjoyable, thus value learning and acquiring language competencies. Additionally, different language contexts should be examined by future research to know the educational benefits and implications of these strategies.